Some intuitionist linguistic aggregation operators - Phong, Pham Hong; Cuong, Bui Cong (Journal of Computer Science and Cybernetics, 2014)
Information aggregation is a usual task in human activity. Linguistic aggregation operators are used to aggregate information given in terms of linguistic labels. The use of linguistic labels has been posed due to the nature of the information or the habit of experts when they give assessments. In this paper, the notion of intuitionist linguistic label is first introduced. This notion may be useful in situations when evaluations of experts are presented as two labels such that the first expresses the degree of membership, and the second expresses the degree of non-membership as in the intuitionist fuzzy theory [1, 2]. Some intuitionist linguistic aggregation operators are also proposed.